EKSPLORASI MIKROBA EPIFIT, ENDOFIT DAN RIZOSFER DARI BERBAGAI SUMBER PADI GOGO DI KECAMATAN KULAWI KABUPATEN SIGI - Jumardin Jumardin; Fathurrahman Fathurrahman; Indrianto Kadekoh; Andi Ete (Jurnal Agrotech, 2018)
Exploration carried out in the filosphere area (leaves) and rhizosphere area (roots) in upland rice plants to get the type of microbes that have potential that can be utilized as biological fertilizer sources, such as N2 fastening microbes, plant growth microbes or phosphate solvent microbial as well as those acting as natural enemies. The research was conducted by location survey method. Determination of location is done by purposive sampling, which is the location of upland rice cultivated by farmers in Kulawi District. The results showed that 10 isolates were isolated from epiphytic and endophytic microbes and endophytes. Morphological tests showed differences in color, shape, elevation, edge, texture and size and the coloring test showed that the bacteria had Coccus cell forms, Bacill, Diplococcus and Semi-Bacillus.